2010
DOI: 10.1021/jp1032965
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Docking/Scoring Scheme Based on the Semiempirical Quantum Mechanical PM6-DH2 Method Accurately Covering Dispersion and H-Bonding: HIV-1 Protease with 22 Ligands

Abstract: In this study, we introduce a fast and reliable rescoring scheme for docked complexes based on a semiempirical quantum mechanical PM6-DH2 method. The method utilizes a PM6-based Hamiltonian with corrections for dispersion energy and hydrogen bonds. The total score is constructed as the sum of the PM6-DH2 interaction enthalpy, the empirical force field (AMBER) interaction entropy, and the sum of the deformation (PM6-DH2, SMD) and the desolvation (SMD) energies of the ligand. The main advantage of the procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
161
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(165 citation statements)
references
References 79 publications
4
161
0
Order By: Relevance
“…[3] These quantities are not only difficult to calculate but also at least one order of magnitude larger than the experimental absolute binding free energy. [69] Even worse, the difference between a tight-binding inhibitor (low nanomolar activity) and the weakest experimentally detectable ligand (an activity of about 100 mm), that is, the so-called "window of activity" is only about 5 kcal mol À1 . [70] Bearing in mind that some of the terms listed above harbour an uncertainty of AE 1-2 kcal mol À1 , the error propagation may lead to a total uncertainty of approximately 5 kcal mol À1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] These quantities are not only difficult to calculate but also at least one order of magnitude larger than the experimental absolute binding free energy. [69] Even worse, the difference between a tight-binding inhibitor (low nanomolar activity) and the weakest experimentally detectable ligand (an activity of about 100 mm), that is, the so-called "window of activity" is only about 5 kcal mol À1 . [70] Bearing in mind that some of the terms listed above harbour an uncertainty of AE 1-2 kcal mol À1 , the error propagation may lead to a total uncertainty of approximately 5 kcal mol À1 .…”
Section: Methodsmentioning
confidence: 99%
“…[78] The SQM scoring was developed further in our group by combining the advanced empirical corrections to the SQM methods (see above) with a refined QM-based scoring function. [69] Like the previous approaches, [79,80] our QM scoring function is designed as a sum of the gas-phase interaction energy, the solvation/desolvation free energy, the change of the conformational "free" energies of the protein and ligand and the entropy change upon binding. Such a decomposition of the binding free energy (approximated by the score) reflects the phenomenological decomposition of an idealised binding process (Figure 3).…”
Section: Qm-based Scoringmentioning
confidence: 99%
“…17,18,19 They also employ the more recent PM6 20 method with corrections for dispersion and hydrogen-bond interactions (DH2). 21,22 They use a single minimised structure of the complex, 3 although they have shown that energies calculated from a minimised structure of the ligand deviates by 13 kJ/mol on average from those calculated on an ensemble of structures from a MD simulation.…”
mentioning
confidence: 99%
“…[72,73] Most interesting are probably the attempts by Hobza and co-workers to develop a reliable docking and scoring scheme based on PM6-DH2, [74,75] and their straight-forward extension of the DH2 model to halogen bonds. [76] One important problem specific to the DH2 model (and other models utilizing charges, such as DH1 and FS1) is the need for charge derivatives to calculate analytical gradients, which is ignored in all current DH2 implementations, but can be quite substantial in the case of strong H bonds.…”
Section: Second-generation Hydrogen-bond Potential Functionsmentioning
confidence: 99%